2023
DOI: 10.3390/su15065146
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Rheology of Synthetic Binder for Sustainable Road Pavements: An Improved Protocol for DSR Testing

Abstract: Bituminous binders are thermal-dependent visco-elastic materials commonly used in pavement engineering. However, synthetic binders represent quite a new family of products that can be used in the substitution of conventional binders with various purposes. Among them, clear synthetic resins recently experienced a quick diffusion since they can be employed in the production of sustainable road pavements (which address aesthetic concerns, thermal aspects, etc.). Since specific studies addressing the rheological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The fixed loading frequency was set at 10 rad/s. The test range spanned from 52 °C to 82 °C, with a test interval of 6 °C [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The fixed loading frequency was set at 10 rad/s. The test range spanned from 52 °C to 82 °C, with a test interval of 6 °C [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was concluded that the application of plastic waste on pavements can reduce costs, conserve natural resources, and improve sustainability despite environmental impact. Pasetto et al [10] stated that synthetic binders may be implemented in place of conventional and sustainable binders. A rheological study was conducted to characterize such materials.…”
Section: Introductionmentioning
confidence: 99%